Pengaruh Work-Life Balance Terhadap Kinerja Karyawan Gen Z: Studi Kasus pada PT XYZ - Zakira, Dhevina Nisa; Chan, Arianis; Muhyi, Herwan Abdul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Changes in work preferences among generation Z have positioned work-life balance as one of the key aspects that companies need to pay attention to. An imbalance between work demands and personal life has the potential to decrease employee performance. This study aims to determine the effect of work-life balance on the performance of generation Z employees at PT XYZ. The research uses a descriptive quantitative approach with a survey method through the distribution of questionnaires. The sampling technique applied is saturated sampling, involving all 42 generation Z employees at PT XYZ. Data analysis was conducted using simple linear regression with the assistance of SPSS version 30. The results indicate that the employees’ work-life balance is in the good category, as is their performance. The coefficient of determination value of 0.431 shows that work-life balance contributes 43.1% to employee performance, while the remaining percentage is influenced by other factors not examined in this study. Therefore, it can be concluded that the better the work-life balance perceived by employees, the higher the level of performance they tend to achieve.